A new integrated multi-objective optimisation algorithm and its application to ship design - Turkmen, B. S.; Turan, O. (Ships and offshore structures, 2007)
This article presents a new integrated multi-objective optimisation algorithm and its application to ship design. The proposed algorithm can successfully introduce designer preferences into the search by modifying elitism and fitness sharing parts of a multi-objective genetic algorithm via a multi-criteria selection method and weighted evaluation of crowding distances. The proposed algorithm is tested, compared and validated against the known methods in the literature and then applied to the internal hull subdivision problem of a Ro-Ro passenger vessel. The internal subdivision of a ship hull is an important measure for the safety of a ship since it directly affects the survivability of a ship when damage occurs. The optimisation problem of the internal subdivision arrangement of ship is successfully solved, and the final solution found via the optimisation study improved the Ro-Ro passenger vessel design from both safety and economical perspectives.